SLA Printed Sub-Terahertz Bifilar Helix Antenna for Radar Imaging - Panusch, David; Bachbauer, Felix; Lomakin, Konstantin; Gold, Gerald (Kleinheubacher Tagung 2023, 2023)
The continuous improvement of additive stereo-lithographic manufacturing (SLA) allows to fabricate filigree sub-Terahertz antennas. This paper presents the first 3D-printed bifilar WR6 helix antenna, which depends on recent developments of printed transition from waveguides to bifilar helices. The measurements of the circularly polarized antenna indicate a −15 dB bandwidth of B15 dB = 10GHz. The axial ratio AR is within B15 dB <3.5dB in the main lobe direction. The achieved linear polarization gain is Glp 14dBi with a circular polarization gain of Gcp 11 to 12 dBi. Due to its small form factor and circular polarization the proposed bifilar helical antenna is suitable for applications in the 120 GHz ISM band, i.e. polarimetric imaging and decomposition as well as broadband communication, e.g. 6G applications.<br
Keywords: Antenna measurements; Waveguide transitions; Polarization; Helical antennas; Imaging; Radar imaging; Radar antennas